(untitled) (European Journal of Health Research, 2021)
Thyroid dysfunctions have been associated with maternal-fetal development abnormalities. The evidence about the influence that thyroid dysfunctions can have on delayed conception is not very numerous. However, the benefit of a systematic screening of such alterations is not well established. The main objective is to determine if thyroid dysfunctions are associated with delays in conception in patients treated in an obstetric clinic.